2003
DOI: 10.1002/ijc.11566
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a naturally occurring constitutively active variant of the epidermal growth factor receptor in mouse fibroblasts increases motility

Abstract: Tumor cell motility is one of the rate-limiting steps of invasion, which defines progression toward a more malignant phenotype. Elevated expression of epidermal growth factor receptor (EGFR) in many cancers is associated with progression of superficial to invasive forms of the disease. The naturally occuring type III mutant epidermal growth factor receptor (EGFRvIII) is a tumor-specific, ligand-independent, constitutively active variant of the epidermal growth factor receptor. EGFRvIII is expressed frequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
1
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 35 publications
5
57
1
1
Order By: Relevance
“…The constitutive TK activity of the EGFRvIII results in the malignant transformation of cells (Han et al, 1996;Nagane et al, 1996;Huang et al, 1997;Antonyak et al, 1998;Montgomery, 2002;Johns et al, 2003;Abulrob et al, 2004;Luwor et al, 2004;Pedersen et al, 2004). In this study, we found that the EGFRvIII is regulated by the Cbl proteins in an identical manner to the WT EGFR.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The constitutive TK activity of the EGFRvIII results in the malignant transformation of cells (Han et al, 1996;Nagane et al, 1996;Huang et al, 1997;Antonyak et al, 1998;Montgomery, 2002;Johns et al, 2003;Abulrob et al, 2004;Luwor et al, 2004;Pedersen et al, 2004). In this study, we found that the EGFRvIII is regulated by the Cbl proteins in an identical manner to the WT EGFR.…”
Section: Discussionsupporting
confidence: 58%
“…Unlike the wild-type (WT) EGFR, the EGFRvIII is unable to bind to EGF or transforming growth factor-α (Ekstrand et al, 1994;Nishikawa et al, 1994;Moscatello et al, 1996) but, instead, it can dimerize spontaneously (Moscatello et al, 1996;Fernandes et al, 2001;Montgomery, 2002). The spontaneous dimerization and ensuing TK activation of the EGFRvIII is necessary to transform cells (Han et al, 1996;Nagane et al, 1996;Huang et al, 1997;Antonyak et al, 1998;O'Rourke et al, 1998;Montgomery, 2002;Johns et al, 2003;Abulrob et al, 2004;Luwor et al, 2004;Pedersen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We tested whether the observed time delay in the motility response of L929 fibroblasts to serum could be reproduced in another fibroblasts cell line, the NR6wtEGFR cell line, which previously has been used to study the molecular mechanisms underlying EGFinduced cell motility [Chen et al, 1994;Pedersen et al, 2004]. From Figure 8, it appears that the motility response of NR6wtEGFR cells to serum was delayed to the same extent as the motility response of L929 cells, indicating that this probably is a general phenomenon.…”
Section: Serum-induced Changes In Fibroblast Motility Require Proteinmentioning
confidence: 97%
“…The epidermal growth factor (EGF) and its receptor (EGFR) constitute a well-characterized receptor-ligand system that plays an important role in the regulation of cell growth, proliferation, survival, and motility (1)(2)(3)(4). EGFR is involved in oncogenic transformation, which can be caused by receptor overexpression, autocrine ligand loops, gene amplification, or activating mutations such as the EGFR type III deletion mutant (EGFRvIII; refs.…”
Section: Introductionmentioning
confidence: 99%